Analisa Pengendalian Bahan Baku Menggunakan Metode Economic Order Quantity di PT. Green Enterprises Indonesia - Putra, Gaustama; Rofita, Riwi (Universitas Teuku Umar, 2020)
High market demand causes problems in production activities without being realized by the company. One of the problems often faced by companies in the occurrence of shortages and excess inventory of raw materials which results in the company being less productive in its production process. Good and correct management of raw materials will help smooth the production process so that consumer orders can be fulfilled with a relatively faster time. Economic Order Quantity (EOQ) is a method used to optimize the purchase of raw materials that can reduce inventory costs so that inventory efficiency in the company can run well. PT. Green Enterprises Indonesia is a coconut oil company that manufactures Virgin Coconut Oil (VOC) products. In 2018, buying 1,870 tons of raw materials with a frequency of ordering 216 times with a total cost of purchasing raw materials Rp. 3,224,558,475. Based on calculations using the EOQ method obtained for raw material needs of 1435 tons, the order frequency is 208 times with a total cost of Rp. 3,183,956,876. From the calculations it can be concluded that there are savings of raw materials as much as 435 tons, ordering frequency 8 times with savings of Rp. 40,601,599. The safety stock is 5.89 tons of coconut and the Re-Order Point is 25.36 tons of coconut.